Endoscopic Ultrasound-Guided Therapies in Pancreatic Neoplasms. (31st January 2015) - Yang, Dennis; DiMaio, Christopher J.
Abstract : Endoscopic ultrasound (EUS) has evolved from being primarily a diagnostic modality into an interventional endoscopic tool for the management of both benign and malignant gastrointestinal illnesses. EUS-guided therapy has garnered particular interest as a minimally invasive approach for the treatment of pancreatic cancer, a disease often complicated by its aggressive course and poor survival. The potential advantage of an EUS-guided approach revolves around real-time imaging for targeted therapy of a difficult to reach organ. In this review, we focus on EUS-guided therapies for pancreatic neoplasms.